2020
DOI: 10.3390/en13215551
|View full text |Cite
|
Sign up to set email alerts
|

Where Renewable Energy Sources Funds are Invested? Spatial Analysis of Energy Production Potential and Public Support

Abstract: Energy transition in the European Union (EU) is strongly related to public support from structural funds which enable member states to create new and renovate existing renewable energy source (RES) installations. However, in order to maximize benefits of these investments it is crucial to consider where RES funds are allocated, how it corresponds with RES potential in specific locations, and how future implementation of energy policies can be improved. In this study, RES development projects supported by EU fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…This indicates that in the analyzed period, the decisions on allocating public funds were not taken on the basis of the anticipated amount of reduction related to the amount of outlays. This conclusion is also confirmed by the research of Nigohosyan et al (2021), who showed the lack of relation between the impact of the size of financing grants and energy savings on the example of enterprises in Bulgaria [38], and Kazak et al (2020), who showed that there is no correlation between the cost of financing renewable energy source installations and energy production potential [39].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This indicates that in the analyzed period, the decisions on allocating public funds were not taken on the basis of the anticipated amount of reduction related to the amount of outlays. This conclusion is also confirmed by the research of Nigohosyan et al (2021), who showed the lack of relation between the impact of the size of financing grants and energy savings on the example of enterprises in Bulgaria [38], and Kazak et al (2020), who showed that there is no correlation between the cost of financing renewable energy source installations and energy production potential [39].…”
Section: Discussionmentioning
confidence: 61%
“…In the authors' opinion, grant financing should be based on benchmarking of efficiency and rigorous energy audit methodology. Other research indicated that there is no correlation between the cost of financing renewable energy source installations and energy production potential, which should be changed in the future energy policy [39].…”
mentioning
confidence: 99%
“…Our research showed that, however, there is a disparity be-tween EU countries, which is influenced by many factors. As is shown in the literature, EU funds in the field of RES have different success rates in Member States EU [99][100][101][102][103].…”
Section: Discussionmentioning
confidence: 91%
“…The vast majority of information, policies, and subsidy programmes that encourage investment and participation in renewable energy generation are typical. Relatively often, this means supporting selected energy sources without taking into account the local context that predestines a given area to use a variety of RES (Chodkowska-Miszczuk, 2019 ; Kazak et al, 2020 ). However, it should be noted that current attempts by the media to improve knowledge of the low-carbon economy are promising.…”
Section: Discussionmentioning
confidence: 99%